2023
DOI: 10.1186/s12889-023-15221-w
|View full text |Cite
|
Sign up to set email alerts
|

Media regulation strategies in parents of 4- to 16-year-old children and adolescents: a cross-sectional study

Abstract: Background Since children can only control and limit their own media use to a limited extent, it is often the parents who regulate their children’s media use. However, there is insufficient research on which strategies they use and on how these strategies are related to socio-demographic and behavioral parameters. Methods The parental media regulation strategies co-use, active mediation, restrictive mediation, monitoring, and technical mediation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…7 It is also possible that parents who use digital media more frequently may be more open to children's media use and impose fewer restrictions. 13 Mealtime & bedroom screen use Family mealtime screen use and child bedroom screen use were both positively associated with adolescent total screen time and problematic use of social media, video game, and mobile phone, which is in accordance with prior evidence. 6,10,11,15,38 The American Academy of Pediatrics advocates for a Family Media Use Plan which notes that parents may consider instituting screen-free times such as during mealtime and bedtime.…”
Section: Parental Screen Time Modelingsupporting
confidence: 86%
See 3 more Smart Citations
“…7 It is also possible that parents who use digital media more frequently may be more open to children's media use and impose fewer restrictions. 13 Mealtime & bedroom screen use Family mealtime screen use and child bedroom screen use were both positively associated with adolescent total screen time and problematic use of social media, video game, and mobile phone, which is in accordance with prior evidence. 6,10,11,15,38 The American Academy of Pediatrics advocates for a Family Media Use Plan which notes that parents may consider instituting screen-free times such as during mealtime and bedtime.…”
Section: Parental Screen Time Modelingsupporting
confidence: 86%
“…These findings were consistent with various prior studies, which have suggested that greater parental screen time use is associated with greater screen time in younger children 17,18,20,37 and more frequent co-use of screens with children. 13 These associations could potentially be explained in the context of social learning theory, which states that individuals learn from observing and modeling other's behavior. Children may mirror parental behavior and could thus model their parents' screen use behaviors.…”
Section: Parental Screen Time Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the parental mediation theory for the digital age and the regulating techniques used by parents of young people can shed light on the constraints and intricacies of electronic media processes (Poulain et al, 2023;Clark, 2011). Furthermore, a meta-analysis of how electronic devices affect students' academic performance and interpersonal connections as well as parental mediation can provide insightful information about the limitations of electronic media processes (Chen & Shi, 2018;Alkandari & Al-Alawneh, 2019).…”
Section: Limitation the Process In Media Electronicmentioning
confidence: 99%